Advanced Intelligent Paradigms in Computer Games - Baba, Norio; Handa, Hisashi (Studies in Computational Intelligence, 2007)
This book presents a sample of the most recent research concerning the application of computational intelligence techniques and internet technology in computer games. The contents include: COMMONS GAME in intelligent environment Adaptive generation of dilemma-based interactive narratives Computational intelligence in racing games Evolutionary algorithms for board game players with domain knowledge The ChessBrain project Electronic market games EVE's entropy Capturing player enjoyment in computer games This book is directed to researchers, practicing engineers/scientists and students.